Understanding students' conceptions of plant reproduction to better teach plant biology in schools. Issue 3 (5th July 2019) - Lampert, Peter; Scheuch, Martin; Pany, Peter; Müllner, Bernhard; Kiehn, Michael
Societal Impact Statement: It is critical that people understand the importance of plants to all life on Earth, and this must be taught in an understandable and engaging way at an early age. Plant reproduction provides useful real‐life examples for teaching students about the biology of plants. However, what do students actually know about this process? We asked students to complete one of three writing tasks to ascertain their understanding of plant reproduction. Their responses provide useful insight into their conceptions of plant reproduction. Ultimately, better knowledge of students' conceptions of topics like plant reproduction can provide educators with important insights to help guide and improve teaching of plant biology in schools. Summary Teaching botany is a challenge due to the phenomenon of "plant blindness" and students' general lack of interest in plants. The reproduction of flowering plants can serve as a useful topic for teaching botany by providing a real‐life context to aid learning. However, research has shown that students have difficulties in understanding how the stages of plant reproduction are connected. This study aims to examine students' conceptions of the processes of plant reproduction. Students' conceptions were analyzed in a multi‐method approach. A total of 724 students from fifth to 12th grade (aged 10–18 years) were assessed using three different types of writing and drawing tasks. Students' conceptions were analyzed in a qualitative content analysis. Results show that students struggle to differentiate between pollination and seed dispersal. Moreover, students have better knowledge about the function of seeds than about the function of pollen. Students are most familiar with seed dispersal by wind and pollination by bees. Better knowledge of students' conceptions can greatly aid teaching. Students' awareness of the function of seeds can be used as a starting point for teaching plant reproduction. The writing and drawing tasks of the study can be used in class to assess students' conceptions in an easy way to make conceptions and their development visible to both students and teachers. Knowledge about students' conceptions of plant reproduction can serve as a basis for deeper understanding and improve how plant biology is taught in schools. Abstract : It is critical that people understand the importance of plants to all life on Earth, and this must be taught in an understandable and engaging way at an early age. Plant reproduction provides useful real‐life examples for teaching students about the biology of plants. However, what do students actually know about this process? We asked students to complete one of three writing tasks to ascertain their understanding of plant reproduction. Their responses provide useful insight into their conceptions of plant reproduction. Ultimately, better knowledge of students' conceptions of topics like plant reproduction can provide educators with important insights to help guide and improve teaching of plant biology in schools.